2021
DOI: 10.1029/2021jb022377
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adria Plate Lithospheric Structures on the Recent Dynamics of the Central Mediterranean Region

Abstract: In the geodynamic context of the slow convergence between the African and Eurasian plates, the Central Mediterranean region has been involved in a complex subduction process that over the last 30 Myr was characterized by the rapid retreat of the Ionian trench, the opening of back-arc extensional basins (i.e., Liguro-Provençal, Algerian, and Tyrrhenian basins) and episodes of slab lateral tearing, segmentation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 119 publications
(271 reference statements)
4
22
0
Order By: Relevance
“…The P ‐wave anisotropic structure agrees well with geodynamic models of the region (e.g., Lo Bue et al., 2021 ), according to which the anisotropic patterns can be interpreted with sub‐vertical flows generated by subduction and the presence of horizontal flows of asthenospheric material around the main slabs related to the pressure exerted by their Mid‐to‐Late Cenozoic horizontal motion. This is true especially in the Central‐Eastern Alpine and Calabrian arcs where the fast azimuths preferentially orient trench‐parallel.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The P ‐wave anisotropic structure agrees well with geodynamic models of the region (e.g., Lo Bue et al., 2021 ), according to which the anisotropic patterns can be interpreted with sub‐vertical flows generated by subduction and the presence of horizontal flows of asthenospheric material around the main slabs related to the pressure exerted by their Mid‐to‐Late Cenozoic horizontal motion. This is true especially in the Central‐Eastern Alpine and Calabrian arcs where the fast azimuths preferentially orient trench‐parallel.…”
Section: Discussionsupporting
confidence: 85%
“…At depths greater than 400 km further differences between the fast anomalies in the two models are found in the western part of the study region (Figure S11 in Supporting Information S1 ). As demonstrated by previous studies (e.g., Faccenna et al., 2001 ; Lo Bue et al., 2021 ) this area, at these depths, is mainly influenced by the presence of the stagnating Ionian slab lying beneath the Central Mediterranean basin as in model ani‐NEWTON21 and not beneath Southern France and Northern Spain as in model iso‐NEWTON21 where such fast anomalies appear to be artifacts due to having neglected the seismic anisotropy. The fact that fast anomalies appear to be mildly affected by including anisotropy can be explained with the strong temperature difference (up to 1000°C) likely existing between the slab cold core and the surround hot mantle.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In order to test the limitations of the tomographic and numerical modeling methods, a promising approach is combining micro-and macro-scale geodynamic modeling simulations of mantle flow to predict mantle isotropic and anisotropic structures and then perform seismological synthetics (Faccenda andCapitanio, 2012, 2013;Hu et al, 2017;Confal et al, 2018;Zhou et al, 2018;Lo Bue et al, 2021). We decided to apply this combined methodology to the Central-Western Mediterranean (CWM) region (Supplementary Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…We first extend the modeling methodology of Lo Bue et al (2021) to create a geodynamic model that resemble observed slabs morphology and anisotropic mantle fabrics of the CWM. The geodynamic model is then exploited as synthetic case study to test the capabilities and limitations of P-waves isotropic and anisotropic inversions in recovering complex geological scenarios using the methodology of VanderBeek and Faccenda (2021).…”
Section: Introductionmentioning
confidence: 99%